2002
DOI: 10.1046/j.0022-3042.2001.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ca2+ and calmodulin‐dependent enzymes in the regulation of glycine transport in Müller glia

Abstract: Glycine (Gly) is considered an obligatory co-agonist at NMDA receptors. Mü ller glia from the retina harbor functional NMDA receptors, as well as low and high affinity Gly transporters, the later identified as GLYT1. We here studied the regulation of Gly transport in primary cultures of Mü ller glia, as this process could contribute to the modulation of NMDA receptor activity at glutamatergic synapses in the retina. We demonstrate that neither glutamate stimulation nor the activation or inhibition of protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 108 publications
(104 reference statements)
1
11
2
Order By: Relevance
“…We have previously demonstrated that GLYT1 function in Mu¨ller cells from the retina (the only other type of radial glia present in the differentiated CNS), is under the control of CaMKII, through the Ca 2+ -activation of CaM (44). Although we showed here that calcium released from intracellular pools and the subsequent activation of CaM are required for transport activity, the inhibition of calmodulindependent kinases by KN-62 did not affect transport (Table III).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We have previously demonstrated that GLYT1 function in Mu¨ller cells from the retina (the only other type of radial glia present in the differentiated CNS), is under the control of CaMKII, through the Ca 2+ -activation of CaM (44). Although we showed here that calcium released from intracellular pools and the subsequent activation of CaM are required for transport activity, the inhibition of calmodulindependent kinases by KN-62 did not affect transport (Table III).…”
Section: Discussioncontrasting
confidence: 62%
“…4. Glutamate and GABA transporters have been shown to be regulated by PKC and by PKC/ PKA, respectively, whereas glycine transport in Mu¨ller glia seems to be regulated by CaMKII (44). We showed that in Bergmann glia, glycine transport was not modified when cAMP intracellular concentration was increased by the addition of 1 mM dibutyryl cAMP or by the stimulation of adenlylyl cyclase with 5 lM forskolin or its inhibition by SQ-22536 (not shown).…”
Section: Regulation By Kinase-activated Intracellular Pathwayscontrasting
confidence: 54%
“…For NET, CaMKII has been shown to in vitro phosphorylate a peptide corresponding to a segment of the NET C-terminal, and stimulation of CamKII activity in PC12 cells, which endogenously express NET, correlates with enhanced NET transport activity (Uchida et al, 1998). Likewise, for GLYT1, a study on GLYT1-expressing glia cells demonstrated reduced Gly uptake upon CaMKII inhibition, but no link to direct transporter phosphorylation was established (Gadea et al, 2002). For SERT, CaMKII activity has been found to regulate the electrophysiological properties of the transporter by modulating the interaction of SERT with syntaxin-1a (section V.G).…”
Section: Phosphorylation a Protein Kinase C-mediated Phosphorylationmentioning
confidence: 99%
“…A few recent studies have associated calcium/calmodulin-dependent protein with glial cells in functions such as actin cytoskeleton remodeling, glutamate and glycine transport, and regulation of neurotrophic factors [59,60,61,62]. This involves the activation of the PI3K protein which, according to Pérez-Garcia et al [62], is regulated by calmodulin proteins associated with calcium.…”
Section: Discussionmentioning
confidence: 99%